STATISTICAL AND EMPIRICAL ANALYSIS OF THE RELATIONSHIP BETWEEN CONATIVE TRAITS AND CRIMINAL BEHAVIOR - Urunov Aziz Shakirovich (Sciental Journals Publishing, 2025)
This article investigates the statistical-empirical relationship between conative traits and criminal behavior. The study focuses on identifying how individual volitional characteristics, such as self-regulation, goal-directed activity, and decision-making, influence tendencies toward antisocial or criminal acts. Using validated psychometric tools and empirical data collected from adolescents and young adults, the research examines correlations between conative components and the manifestation of deviant behavior. The results reveal significant links between low self-control, insufficient goal orientation, and a higher likelihood of engaging in criminal activity. The study emphasizes the importance of integrating psychological, social, and legal perspectives to understand and prevent juvenile delinquency and deviant behavior. The findings provide a scientific basis for developing interventions and programs aimed at strengthening conative capacities and reducing criminal tendencies among youth.
Keywords: Conative traits, volitional activity, self-regulation, criminal behavior, juvenile delinquency, empirical analysis, statistical correlation, antisocial tendencies, behavioral psychology, youth studies.